2015
DOI: 10.1007/s00264-015-2808-5
|View full text |Cite
|
Sign up to set email alerts
|

Triple attack technique for non-union of femoral neck fractures

Abstract: The present study provides encouraging clinical and functional results to suggest that this newly described procedure ('triple attack') might be a valuable option in the management of non-united femoral neck fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…His Harris hip score was 83 a single angled blade plate/sliding hip screw. Pre-bent doubleangled DCS and contoured dynamic compression plates have also been reported in with successful results [23,24].…”
Section: Choice Of Implantmentioning
confidence: 98%
“…His Harris hip score was 83 a single angled blade plate/sliding hip screw. Pre-bent doubleangled DCS and contoured dynamic compression plates have also been reported in with successful results [23,24].…”
Section: Choice Of Implantmentioning
confidence: 98%
“…The above information suggested that blindly increasing stability would not bring benefits to fracture healing, which was also demonstrated in this study. With the persist assistance of BS, the mechanical strength of IMN increased [40]. But the average union time of the BS group (88.5 vs. 97 min, p < 0.001) was significantly longer than that of the BP group.…”
Section: Discussionmentioning
confidence: 89%
“…Surgical management of such a case was challenging due to the patient's young age, bone quality, and underlying GD. The surgical options included fixation of the femoral neck fracture with or without subtrochanteric valgus femoral osteotomy and grafting, 3 but the poor bone quality was concerning in view of a probable delayed or failed union. Also, this surgery would not address the leg-length discrepancy and limping.…”
Section: Case Descriptionmentioning
confidence: 99%